A study on service quality dimensions towards customers’ satisfaction of Air Asia at Kuala Lumpur International Airport 2 / Kartini Afiqah Ahmad Budaya - Ahmad Budaya, Kartini Afiqah (Faculty of Business and Management, 2015)
Number of airlines has been increasing throughout the year. Customers have multi-choices to travel with in choosing airlines either with low-cost carriers (LCCs) or even Full-Service Carriers (FSCs). In order to deliver better quality service to the customers it is imperative for the airlines companies to survive and strengthen their competitive in the airlines industry. Moreover, low-cost airlines have become dominant players in the airlines industry throughout the recent years. An example of low-cost airlines is Air Asia, which have become the main airlines for customers to fly with. Therefore, the purpose of this research is to study the customers’ view on service quality provided by Air Asia. The research was conducted at KUALA LUMPUR INTERNATIONAL AIRPORT 2 (KLIA 2), the main hub for Air Asia. The number of population was 180 and 120 respondents involved in this research for answering questionnaires but only 110 was returned. The sampling technique used was the non-probability sampling which is convenience sample. This research is to explore the dimension of service quality. Hence, this study is to examine the level, relationship and most influence service quality towards customers’ satisfaction for choosing Air Asia at KUALA LUMPUR INTERNATIONAL AIRPORT 2. The findings found Assurance have high level of customers’ satisfaction, all service quality dimensions have positively and strongly relationship with customers’ satisfaction and Empathy is the most important factors towards customers’ satisfaction on Air Asia.